Efektivitas Pemberian Virgin Coconut Oil (Vco) dengan Tingkat Kejadian Ruam Popok Pada Pasien Diare Anak - Noviana Nandari; Nurul Istiqomah; Rusiana Sri Haryanti (PPNI UNIMMAN, 2024)
Diarrhea is the second leading cause of death in children under five years of age. According to WHO (2017) worldwide there are approximately 1.7 billion cases of diarrhea in children each year. In Indonesia, the incidence of diarrhea in toddlers is 23.8%, down from the previous year of 28.9%, still not in accordance with the maximum target set at 20%. The incidence of diarrhea in Karanganyar Regency is 15.30%. Children with diarrhea are prone to diaper rash. One of the treatments for the diaper room is using non-pharmacological therapy by administering virgin coconut oil to maintain the moisture of the child's skin. The effectiveness of administering VCO oil in reducing the incidence of diaper rash in children with diarrhea. Pre-experimental design with one group pre-test post-test design, Sampling technique with total sampling and Data analysis using the Wilcoxon test. Obtaining a p value of 0.000 <0.05, the test decision is Ho is rejected, so it is concluded that there is an effect of administering VCO in reducing the incidence of diaper rash in children with diarrhea at the PKU Muhammadiyah Karanganyar Hospital. diaper rash levels after VCO administration decreased compared to diaper rash levels before VCO administration.